Essential system administration pocket reference - Frisch, AEleen (O'Reilly, 2003)
If you're a Unix system administrator, then the information you need every day just to get your job done could fill a book--a very large book. But, practically speaking, you don't want to stop and thumb through a weighty volume each time a problem arises. Your answer is the Essential System Administration Pocket Reference, the only system administration reference that fits in your pocket. Concise and easy-to-use, this little book is the portable companion to the classic Essential System Administration by AEleen Frisch. The Essential System Administration Pocket Reference is a quick reference to all the fundamental and essential tasks required to run such divergent Unix systems as Solaris, Linux, AIX, BSD, SuSe, Red Hat, and more. Beginners and experienced administrators alike will quickly be able to apply its principles and advice to solve everyday problems. The book is divided into three parts: Commands, Syntax and Their Applications, Configuration Files and Formats, and Operating System Specific Information. The information in this book is a must-have for any administrator or user of a Unix system. O'Reilly's Pocket References have become a favorite among technology professionals everywhere. By providing a wealth of important details in a concise, well-organized format, these handy books deliver just what you need to complete the task at hand. When you've reached a sticking point and need to get to a solution quickly, the new Essential System Administration Pocket Reference is the book you'll want to have.